Evaluation of compounded trilostane packets for dogs with naturally occurring hyperadrenocorticism. (10th June 2021) - Nam, Sookin; Kim, Tae‐won; Song, Kun‐ho; Feldman, Edward C.; Seo, Kyoung‐won
Abstract: Background: Dogs treated for naturally occurring hyperadrenocorticism (NOH) in Korea often appear to require higher doses of trilostane than recommended by authors in the United States, Europe, or the United Kingdom. This phenomenon may be related to compounding trilostane into packets, which is a common practice among veterinary clinics in Korea. Objective: Analyze packets filled by hand and others filled using a semi‐automatic packing device for accuracy of trilostane strength. Animals: Medication packets prepared for 3 dogs with preexisting prescriptions for NOH were analyzed. Method: A trilostane assay was developed for analysis. Trilostane (Vetoryl) capsules were used as clinical controls. Forty‐four medication packets containing trilostane (Vetoryl), prepared by 3 clinicians for 3 dogs with NOH were analyzed. Results: Of 44 trilostane‐containing packets, only 40.9% (18 packets) had acceptable strength of trilostane. Conclusions and Clinical Importance: Clinicians should be aware that compounding trilostane into packets fails to consistently provide measured amounts of trilostane, potentially interfering with response to treatment for NOH in dogs.